ANALISIS KESALAHAN PENGGUNAAN KATA KETERANGAN "GANKUAI" DAN "GANMANG" PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA MANDARIN ANGKATAN 2015 FKIP UNIVERSITAS TANJUNGPURA - Yasya, Nisrina Nabila; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract"Gankuai" and "ganmang" are two words that have similar meanings. They can be added with verbs in the back, but they can not be used interchangeably in terms of usage. Students often do not distinguish their usage in the process of application and learning. So, as a foreign languange student, understanding the utilization of â€œgankuaiâ€ and â€œganmangâ€ are difficult. The author has done a research based on Tanjungpura University students utilization of â€œgankuaiâ€and â€œganmang". Analyzing the misuse of these adverbs. The result showed that the percentage of Tanjungpura University students that are using the word â€œgankuaiâ€ and â€œganmangâ€ are not ideal, correctly rate is only below 50%, mistaken error and misalignment bias rate is also high. There are three reasons for the bias, which is the negative transfer of the mother tongue, the limitation of the language acquisition process and the general grammar rules. Keywords : Adverd, Gankuai, Ganmang, Error analysis